Cloning of the gene encoding Endo-β-1,3-1,4 Glucanase from Bacillus subtilis subsp. spizizenii W23 on Plasmid pMMB67EH into Escherichia coli DH5α and Escherichia coli Origami - Lisa Gunawan (Jurnal Sain Veteriner, 2015)
One of the genes encoding cellulolytic enzymes, named BSUW23_10175, from Bacillus subtilis subsp. spizizenii W23 was cloned in the plasmid pMMB67EH into Escherichia coli DH5α and Escherichia coli Origami. Target gene was amplified using polymerase chain reaction (PCR) with specific primers (For- BSUW23_10175 dan Rev-BSUW23_10175) that were used for BSUW23_10175 gene amplification. Based on the PCR and restriction analyses of the transformants plasmid, it was known that clones number 8 and 9 of the Escherichia coli Origami transformants contained the recombinant plasmid pMMB_BSUW23_10175.Cellulolytic activity assay showed that those transformants had cellulolytic activity by indution with IPTG (isopropyl-β-D-thio-galactosidase).